The effect of exercise intensity types on the self-rated health status of young-old comorbidities patients: a cross-sectional study in Guangdong, China - Linjin Li; Fengfeiyue Dai; Dan Zhang (Frontiers Media S.A., 2023)
ObjectiveExplore the effect of different types of exercise intensity on the self-rated health status of young-old comorbid patients with cardiovascular disease and metabolic disease, as well as the differences in effect among different genders. Provide more references and suggestions for chronic disease management in older comorbidities patients based on the results of the study.MethodsA multi-stage stratified cluster random sampling method was used to select older (≥60 years old) comorbidities patients from communities in Guangdong Province as the survey subjects. Using the "Survey Questionnaire on the Current Status and Influencing Factors of older Comorbidities Patients," face-to-face interviews were conducted with 1,300 old patients. Data from 965 young-old patients (aged 60-74) who simultaneously suffered from cardiovascular and metabolic diseases were selected. Unordered multifactor Logistic regression analysis was used to explore the association between the type of exercise intensity and self-rated health. Stratified analysis was performed based on gender.ResultsThe results of unordered multivariate logistic regression analysis showed that compared with young-old comorbidities patients with poor self-rated of health status, young-old comorbidities patients who underwent vigorous-intensity exercise were more likely to have better self-rated of health status (OR = 4.368, 95% CI: 2.491-7.661, p < 0.05). Stratified analysis based on gender showed that for young-old comorbidities male patients, those who engaged in vigorous-intensity exercise were more likely to have better self-rated of health status (OR = 2.924, 95% CI = 1.266-6.751, p < 0.05); for young-old comorbidities female patients, those who were encouraged by their family to exercise (OR = 2.460, 95% CI: 1.143-5.291, p < 0.05), participate in social activities (OR = 6.173, 95% CI: 2.285-16.678, p < 0.05), and engage in vigorous-intensity (OR = 4.232, 95% CI: 1.869-9.583, p < 0.05) or moderate-intensity exercise (OR = 4.555, 95% CI: 1.825-11.368, p < 0.05) were more likely to have better self-rated of health status.ConclusionIf the physical condition allows, vigorous-intensity exercise has a significant positive effect on the self-rated of health status of young-old comorbidities patients with cardiovascular disease and metabolic disease. Specifically, for young-old comorbidities male patients, those who engage in vigorous-intensity exercise are more likely to self-evaluate their health as good; for young-old comorbidities female patients, both vigorous-intensity and moderate-intensity exercise can improve their self-rated of health status.